Comparative Analysis of Crestal Bone Levels of Basal Implants and Conventional Implants: A Clinico Radiological Study - Kshitibhushan Singh Pandaw; Sachin K Malagi; Dennis V Abraham; Saurabh Tembhurne; Sneha Banerjee; Arundhuti Mahato (Journal of Pharmacy and Bioallied Sciences)
Introduction: This study presents a comparative analysis of crestal bone levels, keratinized gingiva width (KGW), and gingival thickness (BGT) between basal and conventional dental implants over a 6-month period in the mandibular posterior region. Materials and Methods: A total of 20 patients were divided into two groups: Group A (basal implants) and Group B (conventional implants). Both groups underwent flapless implant placements, with immediate loading for basal implants and delayed loading for conventional implants. Results: The results demonstrated significant differences in crestal bone levels, KGW, and BGT between the two groups. The basal implant group exhibited greater mean changes in crestal bone levels (0.35 mm), KGW (0.27 mm), and BGT (0.30 mm) compared to the conventional implant group. These findings suggest a potentially higher risk of bone loss and soft tissue alterations with basal implants, likely due to the biomechanical stresses associated with immediate loading. Conclusion: The study concludes that while basal implants offer the advantage of immediate loading, they may also present challenges related to bone and soft tissue stability.